ANALISIS PERANCANGAN TUNGKU PENGECORAN LOGAM ALUMUNIUM BERBAHAN BAHAN BAKAR OLI BEKAS GUNA MENEKAN BIAYA PRODUKSI DALAM PROSES PRODUKSI ALUMUNIUM BATANGAN - H, Setijanen Djoko; Murnawan, Hery; Prasetyo, Agung (JHP17 (Jurnal Hasil Penelitian), 2022)
CV Mandiri Jaya Logam is a home industry which is engaged in metal casting which producesaluminum bars. The use of wood raw materials that is less effective and efficient for burningbased on the use of wood is very large for the production process, the costs used to purchasefuel are relatively expensive, the combustion system that produces high pollution. This type offurnace (crusible) using koi as a liquid aluminum container only has a resistance of 3 monthsand must be replaced. The refractory made of bricks prepared by the koi has cracks so it needsmaintenance every week, as a result of the heat and air pressure of the gasbull not being ableto be properly dampened by the bricks. natural gas and analyze the calculation of the cost ofproduction. The results of the stove design analysis of used fuel oil, wood, natural gas foundthat the stove design with natural gas fuel has good capability and durability, so that whenthe cost of production of natural gas fuel is analyzed, it has an economical cost for themanufacture of aluminum bar products at a price of Rp. 16,947 / kg